High Frequency Electromagnetic Field Induces Lipocalin 2 Expression in - Amaneh Mohammadi Roushandeh; Raheleh Halabian; Jafar Soleimani Rad; Ahmad Mehdipour; Mohammad Reza Nourani; Mehryar Habibi Roudkenar (Iranian Journal of Basic Medical Sciences, 2010)
Objective(s)Neutrophil gelatinase-associated lipocalin (NGAL/Lcn2), comprise a group of small extracellular proteins with a common β-sheet-dominated 3-dimensional structure. In the past, it was assumed that the predominant role of lipocalin was acting as transport proteins. Recently it has been found that oxidative stress induces Lcn2 expression. It has been also proved that electromagnetic field (EMF) produces reactive oxygen species (ROS) in different tissues. Expression of Lcn2 following exposure to electromagnetic field has been investigated in this study. Materials and MethodsBalb/c mice (8 weeks old) were exposed to 3 mT, 50 HZ EMF for 2 months, 4 hr/day. Afterwards, the mice were sacrificed by cervical dislocation and livers were removed. The liver specimens were stained with Haematoxylin- Eosin (H&E) and analyzed under an optical microscope. Total RNA was extracted from liver and reverse transcription was performed by SuperScript III reverse transcriptase with 1 µg of total RNA. Assessment of Lcn2 expression was performed by semiquantitative and real time- PCR.ResultsThe light microscopic studies revealed that the number of lymphocyte cells was increased compared to control and dilation of sinosoids was observed in the liver. Lcn2 was up-regulated in the mice exposed to EMF both in mRNA and protein levels.ConclusionTo the extent of our knowledge, this is the first report dealing with up-regulation of Lcn2 in liver after exposure to EMF. The up-regulation might be a compensatory response that involves cell defense pathways and protective effects against ROS. However, further and complementary studies are required in this regards.